Characterisation of mahua and coconut biodiesel by Fourier transform infrared spectroscopy and comparison of spray behaviour of mahua biodiesel. Issue 2 (3rd March 2016) - Kumar, Gautam; Kumar, Anoop
Abstract : Biodiesel is one of the most promising alternative fuels and occupies a prominent position among the alternatives to conventional petrodiesel fuel owing to various technical and economic factors and efficient analytical techniques that can be used for the quality control of these fuels. In the present work, an experimental method was developed for determining the concentration of Mahua biodiesel and coconut biodiesel in blends with petrodiesel; the method is based on infrared spectroscopy (Fourier transform infrared [FTIR]-attenuated total reflection [ATR]). The Mahua biodiesel and 20 V%V blends with petrodiesel were analysed using FTIR spectroscopy. Spray penetration depths of various spray models are compared with variations in injected pressure. The FTIR results show that the model obtained in this work has a good ability for determining the concentration of Mahua biodiesel in petrodiesel–biodiesel blends. The Mahua oil is taken as a biodiesel in the present study and the Hiroyasu model can be used for predicting the performance of Mahua biodiesel. The Hiroyasu model is found to be the best model among all models studied for high injected pressure. The penetration depth difference of Hiroyasu and Arregle models increased sharply with lapse of time.